Interdependence of structure and physical properties in co-crystals of azopyridines - Aakeröy, Christer B.; Panikkattu, Sheelu; DeHaven, Baillie; Desper, John (My University, 2012)
To establish how intermolecular interactions influence the supramolecular assembly of azopyridines, a total of five co-crystals of 3,3′ and 4,4′-azopyridine; 3,3′-azpy:succinic acid (3,3′-azpy:SA), 3,3′-azpy:adipic acid (3,3′-azpy:AA), 3,3′-azpy:suberic acid (3,3′-azpy:SuA), 3,3′-azpy:sebacic acid (3.3′-azpy:SeA), and 4,4′-azpy:suberic acid (4,4′-azpy:SuA) were synthesized. In all co-crystals of 3,3′-azopyridine, there are infinite 1-D zig-zag tapes composed of alternating 3,3′-azpy and diacids held together by COOHN(py) hydrogen bonds. Neighbouring chains are arranged into 2-D sheets via secondary inter-chain C–H•••O interactions between azopyridine ring hydrogen atoms and carbonyl oxygen atoms in an in-phase manner. However, in the co-crystal of 4,4′-azopyridine:suberic acid, the adjacent chains form 2-D sheets in an out-of-phase motif via two types of inter-chain C–H•••O interactions, i.e. between azopyridine ring hydrogen atoms and carbonyl oxygen as well as hydroxyl oxygen atoms. The structural consistency within the 3,3′-azopyridine co-crystals has made it possible to establish a correlation between melting point of the homomeric molecular solids and co-crystals of the corresponding carboxylic acids.
Keywords: Azopyridines; Co-crystals